Functional optimization of light-activatable Opto-GPCRs: Illuminating the importance of the proximal C-terminus in G-protein specificity - Leemann, Siri; Kleinlogel, Sonja (Frontiers in Cell and Developmental Biology, 2023)
G-protein coupled receptors (GPCRs) are the largest family of human receptors that transmit signals from natural ligands and pharmaceutical drugs into essentially every physiological process. One main characteristic of GPCRs is their ability to specifically couple with different families of G-proteins, thereby triggering specific downstream signaling pathways. While an abundance of structural information is available on GPCR interactions with G-proteins, little is known about the GPCR domains functionally mediating G-protein specificity, in particular the proximal C-terminus, the structure which cannot be predicted with high confidentiality due to its flexibility. In this study, we exploited OptoGPCR chimeras between light-gated GPCRs (opsins) and ligand-gated GCPRs to systematically investigate the involvement of the C-terminus steering G-protein specificity. We employed rhodopsin-beta2-adrenoceptor and melanopsin-mGluR6 chimeras. We discovered a dominant role of the proximal C-terminus, dictating G-protein selectivity in the melanopsin-mGluR6 chimera, whereas it is the intracellular loop 3, which steers G-protein tropism in the rhodopsin-beta2-adrenoceptor. From the functional results and structural predictions, melanopsin and mGluR6 use a different mechanism to bRhod and b2AR to couple to a selective G-protein. Collectively, this work adds knowledge to the GPCR domains mediating G-protein selectivity, ultimately paving the way to optogenetically elicited specific G-protein signaling on demand.